Exploring the Third Delay: An Audit Evaluating Obstetric Triage at Mulago National Referral Hospital - Forshaw, Jennifer; Raybould, Stephanie; Muyingo, Mark; Weeks, Andrew; Byamugisha, Josaphat (BMC Pregnancy and Childbirth, 2016)
Mulago National Referral Hospital has the largest maternity unit in sub-Saharan Africa. It is situated in Uganda, where the maternal mortality ratio is 310 per 100,000 live births. In 2010 a ‘Traffic Light System’ was set up to rapidly triage the vast number of patients who present to the hospital every day. The aim of this study was to evaluate the effectiveness of the obstetric department’s triage system at Mulago Hospital with regard to time spent in admissions and to identify urgent cases and factors adversely affecting the system.
Keywords: Obstetric; Triage